Coordinating economic growth and carbon emission reduction in China: evidence from the optimal levels of energy price distortions - Sha, Ru (Frontiers in Energy Research, 2023)
Distorted energy prices cause resource mismatch and hinder the coordinated development of economic growth and carbon emission reduction (CDEC) in China. Therefore, it is essential to determine the optimal levels of energy price distortions. This paper first measures the price distortions of fossil and renewable energy sources and applies a panel smooth transition regression model to assess the optimal threshold values for the degree of energy price distortions. The results show that (1) Fossil energy price distortions are negative, and the price distortion for renewable energy is positive. (2) Energy price distortions inhibit CDEC, and this effect is regionally heterogeneous. (3) The panel smooth transformation model results indicate that distorted energy prices have a nonlinear impact on CDEC. CDEC is significantly hampered in the low regime by distorted fossil energy prices and facilitated in the high regime. In contrast, the distorted renewable energy price shows positive in the low regime and negative in the high regime. We also obtain the optimal intervals for the degree of energy price distortions that promote CDEC. With the target of "growth" and "carbon reduction", this study provides a reference for improving the energy pricing mechanism and exploring the effective ways of CDEC.